Cartography, Geodesy, and the Heliocentric Theory: Yves Simonin’s Unpublished Papers - Storni, Marco (My University, 2020)
Yves Simonin, a rather obscure professor of hydrography in Bayonne, submitted five scientific papers to the Paris Academy of Sciences between 1738 and 1740, which only survive in the original manuscript versions. The topics Simonin deals with in these texts are essentially three: the rectification of navigation charts of the Southern Sea, the shape of the Earth, and the heliocentric theory. Far from acknowledging Simonin's contribution to the ongoing academic debate as a valuable one, the institution systematically rejected his work. In this paper, I first provide a critical analysis of Simonin's manuscripts. As I argue, their originality lies in the adoption of the perspective of a practitioner of and expert in navigational techniques. I then investigate the reasons behind the Academy's negative reception of Simonin's papers, casting light on the expertise required to participate in academic debates in the mid-18th century, and on the limits set by the institution to the possibility of external intervention.
Keywords: Heliocentric theory; Isaac Newton; navigation; Paris Academy of Sciences; shape of the Earth; Yves Simonin.